Analisis pelaksanaan manajemen berbasis sekolah dalam bidang sarana dan prasarana SDIT MTA surakarta tahun 2022 - Sumayyah, Sumayyah; Atmojo, Idam Ragil Widianto; Rukayah, Rukayah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to describe and explain the supporting and inhibiting factors for implementing school-based management in the field of facilities and infrastructure at SDIT MTA Surakarta in 2022. This research design uses descriptive qualitative research, case study approach. The research subjects were principals, waka sarpras and classroom teachers as informants who carried out of school-based management in the field of facilities and infrastructure, and the research object was SDIT MTA Surakarta. Data collection techniques used are observation, interviews and documentation. The data validity test technique used is method triangulation and source triangulation. The data analysis technique used interactive data analysis techniques. Based on the results of the study, it was concluded that in the implementation of school-based management in the field of facilities and infrastructure at SDIT MTA Surakarta in 2022 most of them had gone well, which included planning, procurement, storage, maintenance, inventory, elimination and supervision of the management of facilities and infrastructure management. The supporting factor is that most of the school's residents in the management of facilities and infrastructure seem to have independence, partnership, participation, openness, and accountability so that schools can fulfill educational goals by completing learning facilities, especially in the field of elementary school of facilities and infrastructure. While the inhibiting factor is the lack of Human Resources to manage a relatively new school.